A rundown of merger target run‐ups. Issue 2 (8th September 2020) - Dutordoir, Marie; Vagenas‐Nanos, Evangelos; Verwijmeren, Patrick; Wu, Betty
Abstract: We provide evidence of a drastic drop in stock run‐ups of U.S. target firms preceding merger and acquisition (M&A) announcements over the past decades. The median target run‐up declines from approximately 10% in the 1980s to 2% after 2010. The trend in target run‐ups cannot be fully explained by deal or firm characteristics associated with deal anticipation. However, it disappears after controlling for changes in the strength of U.S. insider trading regulation over the research period. Further analyses corroborate our conclusion that more stringent insider trading regulation is the most likely explanation for the reduction in target run‐ups.